Large-amplitude dynamic analysis of heterogeneous thin membrane under different loads - Madani Tonekaboni, Seyed Ali; Karimi Eskandary, Peyman; Jahromi, Sara (International Journal of Engineering and Technology, 2014)
Large amplitude vibration of heterogeneous thin membrane is modeled using the Euler-Bernoulli constitutive law. The obtained nonlinear integro-differential equations are solved using finite difference method. Different results of the problem are illustrated for two different external concentrated loads applied on the middle of the membrane including stepwise and half period sinusoidal forces. The effects of time dependency of the applied loads are investigated. The solution is finally verified and it is concluded that the presented solution can be considered as promising method to obtain large amplitude vibration of thin heterogeneous membrane. Keywords: Large Amplitude Vibration; Thin Membrane; Finite Difference Method; Heterogeneity; Sinusoidal Force.